ETNOMATEMATIKA PADA PEMBUATAN BATIK DI PERUSAHAAN TATSAKA CLURING BANYUWANGI SEBAGAI LEMBAR KERJA SISWA - Farida, Yuli; Susanto, Susanto; Setiawan, Toto' Bara (Department of Mathematics Education , University of Jember, 2020)
Ethnomatematics is a science used to understand how mathematics is adapted from a culture. The purpose of this study is to dig ethnomatematics on the making of batik tulis Kangkung Setingkes and create a student worksheet in accordance with the curriculum 2013. This type of research is qualitative with ethnographic approaches. The subject in this study amounted to seven people. Data Collection using observation methods, interviews, and documentation. Data collection results are analyzed descriptively. Based on the analysis of data from the observation and interviews, obtained ethnomatematics in the process of making batik in the Setingkes Kangkung. The meaning of Ethnomatematics is the concept of algebraic and geometric concepts. Algebraic concepts include counting, measuring, and masing and geometry concepts, such as point, line, angle, construction, congruation, and Geometry transformation (translation, rotation, reflection, dilation). Ethnomatematics in this study were made as student worksheets for class VII of comparative material and the XI class of geometry transformation material.